2020
DOI: 10.1016/j.biomaterials.2020.120306
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared fluorescent coatings of medical devices for image-guided surgery

Abstract: Rapidly expanding field of image-guided surgery needs new materials for near-infrared imaging with deep tissue penetration. Here, we introduce near-infrared coating of equipment (NICE) for image-guided surgery based on a series of lipophilic cyanine-7.5 dyes with bulky hydrophobic counterions and a biocompatible polymer, poly(methyl methacrylate). The NICE material exhibits superior brightness (15-20-fold higher) and photostability compared to fluorescent coatings based on commonly used indocyanine green (ICG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 85 publications
3
42
0
Order By: Relevance
“…105 However, to avoid the dye leakage out of the polymer, especially in biological media, the fluorophore and the polymer should be sufficiently hydrophobic to retain the FM through strong hydrophobic interactions. 26,33,104 Although this method can be efficient in the case of polymers possessing a highly hydrophobic matrix are combined with fluorophores with enhanced hydrophobicity, 106 it cannot be applied to all BCP as the FM will escape (Fig. 8) and will thus lead to false conclusions in imaging and potential toxic effects.…”
Section: Nir-ii Dyesmentioning
confidence: 99%
See 1 more Smart Citation
“…105 However, to avoid the dye leakage out of the polymer, especially in biological media, the fluorophore and the polymer should be sufficiently hydrophobic to retain the FM through strong hydrophobic interactions. 26,33,104 Although this method can be efficient in the case of polymers possessing a highly hydrophobic matrix are combined with fluorophores with enhanced hydrophobicity, 106 it cannot be applied to all BCP as the FM will escape (Fig. 8) and will thus lead to false conclusions in imaging and potential toxic effects.…”
Section: Nir-ii Dyesmentioning
confidence: 99%
“…In order to decipher the nature of their interactions in biological media and their biodistribution, the fluorescence labeling of BCP was rapidly considered. Indeed, the fluorescence spectroscopy and microscopy techniques have proven to be powerful tools to study biological mechanisms, 25 interactions between medical devices and tissues 26 and drug release. 27 The fluorescence labeling also allows tracking of copolymers in cellulo and in vivo with a high temporal and spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Again, this process is currently strictly dependent on the surgeon's visual capabilities and anatomical knowledge and currently there are no universally accepted methods to recognize noble anatomical structures intraoperatively. However, several experimental methods using optical imaging modalities, but still requiring an injection of exogenous contrast agents [61][62][63] or the use of fluorescent devices [64][65][66], have been put forward to highlight key anatomical structures within human or experimental models.…”
Section: Tissue Recognitionmentioning
confidence: 99%
“…Earlier works showed that bulky anions could increase performance of NIR dyes of the cyanine family, but these works were done either on pure dye salts 40 or on polymeric coatings at low dye loading. 41 In addition, we intended to implement a covalent PEGylation strategy for these dye-loaded NPs, which has been proven to be fruitful to ensure stealth properties to polymeric NPs. [42][43][44] In the present work, we applied the bulky counterion approach to the encapsulation of two near-infrared dyes based on Cy5.5 and Cy7 into NPs based on the biodegradable polymer PLGA.…”
Section: Introductionmentioning
confidence: 99%